PERANCANGAN SISTEM INFORMASI PEMASARANDI UMKM FAS BOUTIQUE : Marketing Information Sistem;E-Commerce;UML;Agile. - Hidayat, Fendi (JURNAL AKADEMIKA, 2021)
FAS Boutique is one of the MSMEs that is engaged in the manufacture and sale and purchase of clothing. Currently, the sales or marketing system used is still using conventional systems, so it is necessary to develop it so that it uses an online information system. It is hoped that by using an online marketing information system, the marketing reach of Fas Boutique will be wider and the transaction process can be recorded properly. The system is designed using UML and developed with agile methods. as for some of the main features of the system are registration, marketing, sales and reports.